The larva of Eubasilissa maclachlani White 1862 (Trichoptera: Phryganeidae) from Thailand, with notes on its biology - Panich-Pat, Thanawan; Prommi, Taeng On (Zootaxa, 2021)
The final-instar larva of Eubasilissa maclachlani White 1862 is described with illustrations for the first time based on Thai specimens. The larva of E. maclachlani exhibits typical morphological characteristics of Phryganeidae. The morphological characteristics of the larva of E. maclachlani can be seen in the following features: First, the band on the frontoclypeus is anchor-like. Second, the ventral apotome is narrowly triangular. Third, the mesonotum is large and membranous, and the mesonotal sa1 sclerites are contiguous mesally. Fourth, comb-like spines, each consisting of tiny points, are distributed over much of the ventromesal surfaces of the fore- and midcoxae. Finally, the shape of tergite IX is heart-like with reddish brown dots. Larvae of E. maclachlani construct cylindrical cases made from many pieces of plant fragments, fastened together by silk in a ring-like pattern, with five successive rings. The larval habitat and phenology are also briefly discussed.